2017
DOI: 10.3233/jad-170409
|View full text |Cite
|
Sign up to set email alerts
|

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention?

Abstract: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 30 publications
2
43
2
1
Order By: Relevance
“…The young-onset nature of the illness and family heritability in HD may account for the higher baseline of caregiver burden. 25 The development, time-dependency, and physical health dimensions of burden on CBI were specifically increased in the anosognosia group. These dimensions correspond, respectively, to the negative feeling from the deviation from expected caregiver's life development (eg "missing out on life," "expected that things would be different at this point in my life"), the restriction on time, and the physical impact as a consequence of caregiving.…”
Section: Discussionmentioning
confidence: 92%
“…The young-onset nature of the illness and family heritability in HD may account for the higher baseline of caregiver burden. 25 The development, time-dependency, and physical health dimensions of burden on CBI were specifically increased in the anosognosia group. These dimensions correspond, respectively, to the negative feeling from the deviation from expected caregiver's life development (eg "missing out on life," "expected that things would be different at this point in my life"), the restriction on time, and the physical impact as a consequence of caregiving.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have found that caregiver burden is higher in YOD patients. 11,47 Spouses of YOD patients tend to experience a high level of distress, stress, caregiver burden, depression and coping difficulties. 6,11,15,47 Increased caregiver psychological distress can be due to a variety of reasons.…”
Section: Caregiver Distress and Burdenmentioning
confidence: 99%
“…11,47 Spouses of YOD patients tend to experience a high level of distress, stress, caregiver burden, depression and coping difficulties. 6,11,15,47 Increased caregiver psychological distress can be due to a variety of reasons. Spouses of YOD patients often assume additional responsibilities such as caring for children and the patient, becoming the breadwinner, and making important financial and social decisions.…”
Section: Caregiver Distress and Burdenmentioning
confidence: 99%
“…DRP has consistently been associated with greater caregiver burden and more rapid progression to severe dementia, institutionalization, and death. [34][35][36][37][38] Many forms of dementia, aside from VaD, result from neurodegenerative disease and are associated with various proteinopathies characterized by protein misfolding and aggregation. Aberrant aggregated proteins in AD produce β-amyloid plaques and neurofibrillary tangles (hyperphosphorylated tau aggregates).…”
Section: Introductionmentioning
confidence: 99%